Scientific tools for assessing the resource potential of industrial enterprises in Ukraine - Pochtovyuk, Andrii (Narzędzia naukowe służące oszacowaniu potencjału zasobów przedsiębiorstw przemysłowych na Ukrainie, 2021)
The article aims to analyse the development of tools, and assess the resource potential for industrial enterprises in Ukraine, and it also discusses the ways of forming a scientific research methodology. The success of the functioning of an economic entity is determined by the level of resource availability, their structure, the rate of renewal, the efficiency of use and the level of specialization. The scope of an enterprise determines all of these factors by its resource potential. Economists are looking for the best solutions for its evaluation, and thus various ways of previously known and tested methods of improving are proposed. The authors noted that nowadays there is no uniform methodology for assessing the resource potential of an enterprise in the real sector of the economy. The existing measurement tools are the separate indicators that characterize the efficiency of the enterprise. However, for a complete assessment, it should be all-round and systematic. In this regard, the procedure and system of indicators to assess the main types of resources were proposed, which can be applied by any industrial enterprise in order to improve its efficiency.
Biblioteka Regionalisty, 2021, Nr 21, s. 111-123
Keywords: resource potential; indicators of resource evaluation; methods of efficiency evaluation; production resource; labour resources; financial resources; potencjał zasobowy; wskaźnik oceny zasobów; metody oceny efektywności; zasoby produkcyjne; zasoby pracy; zasoby finansowe